2007
DOI: 10.1590/s0074-02762007000800006
|View full text |Cite
|
Sign up to set email alerts
|

Biology of three species of North American Triatominae (Hemiptera: Reduviidae: Triatominae) fed on rabbits

Abstract: Aspects related to hatching, lifetime, number of blood meals for molting, mortality, feeding time, and postfeeding defecation delay were evaluated and compared in each instar of three North American Triatominae:Triatoma gerstaeckeri, Triatoma lecticularia and Triatoma protracta, all of them fed on rabbits. No significant differences (p > 0.05) were found among the three species regarding mean hatching rate, which was close to 20 days. Egg-to-adult development times were significantly shorter (p < 0.05) for T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
2
24
1
4
Order By: Relevance
“…All of the species studied had average incubation periods of approximately 19 days, reflecting the favourability of the maintenance conditions for the development of these species. The egg hatching rate for T. protracta (72.5%) was similar to the rates observed for three related former subspecies of T. protracta (currently synonymised to T. protracta): Triatoma protracta navajoensis Ryckman (74.2%), Triatoma protracta nahuatlae Ryckman (76%) and Triatoma protracta zacatecensis Ryckman (81.9%), all of which were fed on rabbits (Ryckman 1962, Martínez-Ibarra et al 2007). The egg eclosion rate of T. rubida in the current study (72%) was similar to the eclosion rate (70.5%) of the former subspecies Triatoma rubida sonoriana (currently synonymised to T. rubida) found in a previous study of specimens from Caborca, a municipality that is distant from the area from which the founder specimens of our T. rubida colony were collected (Martínez-Ibarra et al 2005).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…All of the species studied had average incubation periods of approximately 19 days, reflecting the favourability of the maintenance conditions for the development of these species. The egg hatching rate for T. protracta (72.5%) was similar to the rates observed for three related former subspecies of T. protracta (currently synonymised to T. protracta): Triatoma protracta navajoensis Ryckman (74.2%), Triatoma protracta nahuatlae Ryckman (76%) and Triatoma protracta zacatecensis Ryckman (81.9%), all of which were fed on rabbits (Ryckman 1962, Martínez-Ibarra et al 2007). The egg eclosion rate of T. rubida in the current study (72%) was similar to the eclosion rate (70.5%) of the former subspecies Triatoma rubida sonoriana (currently synonymised to T. rubida) found in a previous study of specimens from Caborca, a municipality that is distant from the area from which the founder specimens of our T. rubida colony were collected (Martínez-Ibarra et al 2005).…”
Section: Discussionsupporting
confidence: 73%
“…
Biological information is widely available for the 13 most common domestic triatomines (Hemiptera: Reduviidae: Triatominae) among the 30 species described in Mexico (Martínez-Ibarra et al 2007, Salazar-Schettino et al 2010). Information about the remaining species is scarce, primarily because these species have rarely been collected and are difficult to raise under laboratory conditions.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1951 Wood reported the following average postfeeding defecation times (minutes) for the adults of four U.S. species: T. protracta, 30.6 (n ϭ 10); T. rubida, 1.6 (n ϭ 5); T. recurva, 75.7 (n ϭ 3); and P. hirusta, 35.0 (n ϭ 2) (327). In a similar study in 2007 using both nymphs and adults of three Mexican species (also present in the United States), Martinez-Ibarra et al reported the following results: T. protracta, 6.7 (n ϭ 475); T. lecticularia, 8.3 (n ϭ 368); and T. gerstaeckeri, 11.5 (n ϭ 733) (183 (153). In that study, it was noted that none of the bugs of either species defecated on the host during the experiment.…”
Section: Human-vector Interactions and T Cruzi Transmission Potentiamentioning
confidence: 82%
“…If we calculate the same rate in other species of triatomines (sum of developmental periods of 4th and 5th instar nymphs/sum of developmental periods of 1st, 2nd and 3rd instar nymphs) we find that this is not the case for them. (Zeledón et al 1970, Galvão et al 1995, Martínez-Ibarra et al 1999, 2003, 2007, Cabello & Lizano 2001, Rocha et al 2001, Emmanuelle-Machado et al 2002, Wolf et al 2004, LuitgardsMoura et al 2005, Villacis et al 2008). …”
Section: Discussionmentioning
confidence: 99%